Dosing Patterns In Treatment of Disabling Spasticity With Intrathecal Baclofen. Issue 6 (November 2021) - Gunnarsson, Stina; Lemming, Dag; Alehagen, Siw; Berntsson, Shala; Ertzgaard, Per; Samuelsson, Kersti
Abstract: Purpose: The aim of this study was to describe and analyze dosing patterns for patients with ITB treatment over time and to identify possible subgroups demonstrating diversity in patterns. Design: A retrospective design. Methods: For 81 patients from six different hospitals, baclofen doses from the first 2 years of treatment were identified using medical records. Line graphs of each patient's doses were analyzed and grouped based on similarities in dosing pattern. Findings: The analyses of the dosing patterns resulted in four different subgroups classified as stable, slow increase, rapid increase, and fluctuating. Conclusion: The results highlight the clinical challenge of predicting dose development over time. Clinical Relevance to Rehabilitation Nursing: This study provides rehabilitation healthcare professionals with a better understanding of intrathecal baclofen dose development. Illustrations of the four subgroups can be used as an educational tool for patients, family, and caregivers.